Th1-Biased Hepatitis C Virus-Specific Follicular T Helper-Like Cells Effectively Support B Cells After Antiviral Therapy - Zoldan, Katharina; Ehrlich, Sabine; Killmer, Saskia; Wild, Katharina; Smits, Maike; Russ, Marissa; Globig, Anna-Maria; Hofmann, Maike; Thimme, Robert; Boettler, Tobias (Frontiers in Immunology, 2021)
Circulating Th1-biased follicular T helper (cTfh1) cells have been associated with antibody responses to viral infection and after vaccination but their B cell helper functionality is less understood. After viral elimination, Tfh1 cells are the dominant subset within circulating Hepatitis C Virus (HCV)-specific CD4 T cells, but their functional capacity is currently unknown. To address this important point, we established a clone-based system to evaluate CD4 T cell functionality in vitro to overcome experimental limitations associated with their low frequencies. Specifically, we analyzed the transcription factor expression, cytokine secretion and B cell help in co-culture assays of HCV- (n = 18) and influenza-specific CD4 T cell clones (n = 5) in comparison to Tfh (n = 26) and Th1 clones (n = 15) with unknown antigen-specificity derived from healthy donors (n = 4) or direct-acting antiviral (DAA)-treated patients (n = 5). The transcription factor expression and cytokine secretion patterns of HCV-specific CD4 T cell clones indicated a Tfh1 phenotype, with expression of T-bet and Bcl6 and production of IFN-γ and IL-21. Their B helper capacity was superior compared to influenza-specific or Tfh and Th1 clones. Moreover, since Tfh cells are enriched in the IFN-rich milieu of the HCV-infected liver, we investigated the impact of IFN exposure on Tfh phenotype and function. Type I IFN exposure was able to introduce similar phenotypic and functional characteristics in the Tfh cell population within PBMCs or Tfh clones in vitro in line with our finding that Tfh cells are elevated in HCV-infected patients shortly after initiation of IFN-α therapy. Collectively, we were able to functionally characterize HCV-specific CD4 T cells in vitro and not only confirmed a Tfh1 phenotype but observed superior Tfh functionality despite their Th1 bias. Furthermore, our results suggest that chronic type I IFN exposure supports the enrichment of highly functional HCV-specific Tfh-like cells during HCV infection. Thus, HCV-specific Tfh-like cells after DAA therapy may be a promising target for future vaccination design aiming to introduce a neutralizing antibody response.